Front Cover: Crystal Structures and Spin‐Crossover Behavior of Iron(II) Complexes with Chiral and Racemic Ligands (Eur. J. Inorg. Chem. 7/2017). Issue 7 (15th February 2017) - Sekimoto, Yusuke; Karim, Mohammad Razaul; Saigo, Naoto; Ohtani, Ryo; Nakamura, Masaaki; Hayami, Shinya
Abstract : The cover picture shows a Japanese New Year's greeting card symbolizing the dawn of a new era for chiral magnetism. We chose Mt. Aso, which is the symbol of Kumamoto, as the central picture in the background. Structures of two chiral spin‐crossover (SCO) iron complexes are depicted to the left and right of the "dragon". Details are discussed in the article by S. Hayami et al. on page 1049 ff (DOI:10.1002/ejic.201601232 ). For more on the story behind the cover research, see the Cover Profile (DOI:10.1002/ejic.201700131 ).